PENGEMBANGAN KINERJA MELALUI KONDISI KERJA, KONTEN PEKERJAAN DAN PENGEMBANGAN KARIR DENGAN MEDIASI MOTIVASI KERJA - Rini Ardista (Sekolah Tinggi Ilmu Ekonomi Tribuana, 2018)
Human resources is one of the most important assets of an organis=zation. In other words, the success of an organization is highly dependent on the performance if its employees. Therefore, managers and experts seek to determine what factors most influence employee motivation. This study aims to analyze the effect of working condition, jobs content, and carrer development on work. Motivation and perfimance. Respondents in this study were selected by using the method of proporsionate stratified random sampling as many as e137 employees. Based on the result ogthe research shows values of Square ( R2 ) which only career development and work motivation. There are significant positive effect of working condition, job content, career development and joint work motivation toward HR performance